Analysis of Factors Affecting Rice Import Volume in Indonesia - Hisyam, Alif Zainul; M. Taufiq (Cita konsultindo, 2025)
Rice imports are a strategic issue in national food security, especially when domestic production is unable to meet domestic demand. This study aims to analyze the factors that influence the volume of rice imports in Indonesia in the period 1999–2023. The independent variables used in this study include domestic rice production, domestic rice consumption, domestic rice prices, and international rice prices. Meanwhile, the dependent variable is rice imports. The approach used in this study is a quantitative approach with annual secondary data obtained from the Central Statistics Agency (BPS), the Ministry of Agriculture, and the FAO. The data analysis technique used is multiple linear regression with the help of SPSS software version 25. The results of the analysis show that the variables of international rice prices and domestic rice prices have a positive and significant effect on rice imports. Meanwhile, the variables of domestic rice production and consumption do not have a significant effect, but have a negative relationship to import volume. This indicates that Indonesia's dependence on the global market is still high in meeting its rice needs. The coefficient of determination (R²) of 41.6% indicates that variations in rice imports can be explained by the five independent variables. This research provides input for the government to strengthen food security by increasing domestic production and monitoring fluctuations in global rice prices. Keywords: Rice Imports, Production, Consumption, Domestic Rice Prices, International Prices, Land Area